The lawc gene is a new member of the trithorax-group that affects the function of the gypsy insulator of Drosophila. - Zorin, I.D.; Gerasimova, T.I.; Corces, V.G. (Genetics, 1999)
Mutations in the lawc gene result in a pleiotropic phenotype that includes homeotic transformation of the arista into leg. lawc mutations enhance the phenotype of trx-G mutations and suppress the phenotype of Pc mutations. Mutations in lawc affect homeotic gene transcription, causing ectopic expression of Antennapedia in the eye-antenna imaginal disc. These results suggest that lawc is a new member of the trithorax family. The lawc gene behaves as an enhancer of position-effect variegation and interacts genetically with mod(mdg4), which is a component of the gypsy insulator. In addition, mutations in the lawc gene cause alterations in the punctated distribution of mod(mdg4) protein within the nucleus. These results suggest that the lawc protein is involved in regulating the higher-order organization of chromatin.